Students' Perspective Toward the Indonesian National Characters in Pramoedya Ananta Toer's Short Story Entitled "Inem" - Dengah, Linda Chetsiana; Mustofa, Mutmainnah; Zahroh, Latifah Fatimatuz (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This research examines readers’ perspective of 18 Indonesian national characters in Inem, a short story by Pramoedya Ananta Toer. The sample of this research is 34 students of XI Akuntansi Keuangan dan Lembaga of SMKN 1 Pujon. The aim of this research is to analyze whether the students’ perceptions toward Pramoedya Ananta Toer’s short story, entitled Inem match to their understanding on 18 Indonesian national characters. The method used in this research is descriptive qualitative research. The finding of this research states each student has different perception of the Indonesian national characters in the Pramoedya Ananta Toer’s short story entitled Inem. However, most of the students have the same perceptions of the Indonesian national character in the short story entitled Inem. Their perception depends on how they understand the meaning of each of the 18 Indonesian national characters. Therefore, the researcher claims that the students’ perceptions toward Pramoedya Ananta Toer’s short story, entitled Inem match to their understanding on 18 Indonesian national characters.